2015
DOI: 10.1007/s40865-015-0019-9
|View full text |Cite
|
Sign up to set email alerts
|

Arrested Development: Does the Grade Level at Which Juveniles Experience Arrest Matter?

Abstract: Purpose This study examines the effect of arrest on delinquency at a salient transition during adolescence: the move from middle to high school. The effects of arrest on delinquency via deviant attitudes, attenuation of prosocial bonds, and involvement with deviant groups are examined to determine whether labeling processes and consequences vary for youth in 7th, 8th, or 9th grade. Methods Longitudinal data from a school-based survey are used to estimate the direct and indirect effects of arrest on delinquency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…Using propensity score matching, they found that youth who had police contact reported significantly higher levels of delinquency—among other outcomes—than youth without police contact, suggesting that formal contact with the criminal justice system does not serve as a deterrent and actually increases delinquency. Relatedly, Wiley (2015), also using GREAT program data, found that arrest increased delinquency for seventh, eighth, and ninth graders. Further, the author demonstrated that this effect was most pronounced among seventh graders due to its negative effects on attitudes, peer associations, academic achievement, and prosocial activities.…”
Section: Criminal Justice the Life Course And Youthmentioning
confidence: 95%
“…Using propensity score matching, they found that youth who had police contact reported significantly higher levels of delinquency—among other outcomes—than youth without police contact, suggesting that formal contact with the criminal justice system does not serve as a deterrent and actually increases delinquency. Relatedly, Wiley (2015), also using GREAT program data, found that arrest increased delinquency for seventh, eighth, and ninth graders. Further, the author demonstrated that this effect was most pronounced among seventh graders due to its negative effects on attitudes, peer associations, academic achievement, and prosocial activities.…”
Section: Criminal Justice the Life Course And Youthmentioning
confidence: 95%
“…The effect of simply getting arrested, regardless of whether there is a subsequent conviction or sentence, may linger for 2 Tobacco Use Insights months or years adversely affecting a person's life. 10 A label could end up changing a person's life path in that she or he may incur myriad collateral consequences that limit their opportunities, particularly the inability to work in certain professions. [19][20][21] These collateral consequences can result in stress to an individual, which may increase engagement in coping behaviors (eg, smoking) to alleviate the stress.…”
Section: Getting Arrested Incurring a Label And Smokingmentioning
confidence: 99%
“…8 A transition such as arrest could shift a person from one smoking pathway to another as it may result in an individual incurring a label of criminal, 9 regardless of whether or not they were subsequently convicted and sentenced. 10…”
Section: Introductionmentioning
confidence: 99%
“…Research examining the importance of timing of arrest on outcomes finds that the age at which youth first become involved in the juvenile justice system has differential effects on their development. For example, Wiley [92] found that arrest had more pronounced consequences on later delinquent behavior for younger (e.g., seventh grade) compared to older (e.g., eighth and ninth grade) youth. Arrest may be particularly damaging at younger ages and have more serious consequences later in life, including more chronic offending and longer criminal careers [63], dropping out of school [47], later poverty [61], substance use, and unemployment [50].…”
Section: Theoretical Frameworkmentioning
confidence: 99%